Experiences of Intimate Partner Violence Among Lesbian, Gay, Bisexual, and Transgender College Students: The Intersection of Gender, Race, and Sexual Orientation. Issue 11 (June 2021) - Whitfield, Darren L.; Coulter, Robert W. S.; Langenderfer-Magruder, Lisa; Jacobson, Daniel
Lesbian, gay, bisexual, and transgender (LGBT) college students experience disproportionate rates of intimate partner violence (IPV) compared with their heterosexual and cisgender counterparts. Some studies report rates of IPV among lesbian, gay, and bisexual college students as high as 50%, and 9 times greater among transgender students compared with their cisgender peers. Few studies have investigated the impact of intersectional identity on experiencing different types of IPV, such as emotional, physical, and sexual IPV. The present study utilized the National College Health Assessment–II from 2011 to 2013 ( n = 88, 975) to examine the differences in types of IPV among college students based on sexual orientation, gender identity, and the intersection of these two identities. Bivariate Rao–Scott chi-square and multilevel logistic regression was used to test the associations between sexual orientation, gender identity, and the intersection of these identities on multiple types of IPV. Adjusting for covariates and school clustering, LGBT college students had higher odds of reporting emotional IPV (adjusted odds ratios [AORs] = 1.34-1.99), physical IPV (AOR = 1.58-2.93), and sexual IPV (AOR = 1.41-6.18). Bisexual and transgender college students demonstrated the highest odds of reporting IPV based on sexual orientation and gender identity, respectively. Intersectional identities were not significantly associated with IPV. These findings demonstrate a need for clinicians working with college students to be aware of the disproportionate prevalence of IPV among LGBT individuals, particularly for those clients those who identify as bisexual and/or transgender and participate in continuing education related to these populations. Furthermore, these findings illustrate the need for additional intersectional research with LGBT college students.